O estágio supervisionado por entre telas: espaço para compreensões do trabalho docente - Lino, Amanda Alves (2022)
This research has the general objective to understand, through roaming diaries produced by interns, how a curricular component of Remote Supervised Internship contributed to the initial training of students of the Letters - Portuguese course at the Federal University of Paraíba. The study was motivated by the researcher's concerns and perceptions from the formative experiences trodden in the Supervised Internship since graduation. We place ourselves in the field of Applied Linguistics, since we align ourselves with other studies that also deal with the same topic. In addition, we emphasize that research in Applied Linguistics has strengthened, in recent decades, the initial training of teachers and, therefore, the Supervised Internship, we can highlight the contributions of Albuquerque (2007), Menezes (2008), Pimenta and Lima ( 2009) Reichmann (2010), Souza (2014), Sant'ana (2016), Segabinazi (2016), Tanuri (2000). We used a qualitative approach, because its object is in social relationships, in the way the participants behave in their context, in our case, the interns who attended the Supervised Internship curricular component and who made their interventions remotely. To generate data, we participated assiduously in the classes of the curricular component of the Supervised Internship VI of the UFPB Portuguese Language Course in different classes through the Teaching Internship, which allowed us to perceive the interactions, concerns, anxieties and doubts of the interns. As corpus we used eight (8) roaming diaries, prepared by the interns during the curricular component Supervised Internship VI. A sociocultural questionnaire was also applied in order to know the profile of the research collaborators. The data were analyzed in the light of the theoretical-methodological approach of Sociodiscursive Interactionism (BRONCKART, 1999, 2006, 2008, 2015; MACHADO; BRONCKART, 2009) which is recognized as a Science of the Human and which provides an important epistemological basis for understanding issues related to to the Supervised Internship, its nuances and its protagonists; as well as the principles of labor sciences, especially the Activity Clinic (AMIGUES, 2004; MACHADO, 2004, 2007; CLOT, 2007, 2010). The results achieved show us that, even remotely, the internship is a formative space, which contributed significantly to the initial education of the group of interns, enabling them to understand the teaching work and significant implications for their profession, not only in the pandemic context, but in other situations.